DO GENETIC PERSONALITIES AND AUTHORATIVE PARENTING STYLES INFLUENCE CHILDREN’S CHARACTER? A CORRELATIONAL STUDY AT ELEMENTARY SCHOOLS IN INDONESIA - Dewiana Novitasari; Masduki Asbari; Agus Purwanto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
This study aimed to determine the effects of genetic personalities and parenting styles, especially the type of authoritative parenting style on children's character development. This study utilized a correlational method with a quantitative research approach. The data were collected by distributing questionnaires online to the population selected by using a simple random sampling technique. The population of this study was parents of elementary school students for as many as 150 people. The data in this study were analyzed by SEM (Structural Equation Model) with Smart PLS version 3.0 software. The results showed that the genetic personality and the authoritative parenting style had a positive and significant effect on children's character development.